Cohort profile: the Schulthess registries in Zurich for hand implants and forearm corrective osteotomies - Kei Mathis; Daniel B Herren; Stephan Schindele; Miriam Marks (BMJ Open)
Purpose Our hand and forearm registries were established to evaluate safety, function, quality of life and patient satisfaction in patients undergoing thumb and finger implant arthroplasties, as well as corrective osteotomy of the forearm with individual patient solution (IPS) implants.Participants Four registries were initiated between 2010 and 2020 and enrolled patients who underwent implant arthroplasties of the thumb carpometacarpal (CMC) joint (n = 486), proximal interphalangeal (PIP) or thumb interphalangeal (IP) joint (n = 864) and metacarpophalangeal (MCP) (n = 34) joint, as well as 27 patients who underwent corrective osteotomy of the distal radius or forearm using an IPS implant. All patients complete disease-specific questionnaires and undergo clinical assessment before surgery (baseline) and up to 10 years thereafter.Findings to date All operated patients (100%) were included in the registries with complete baseline data. One-year follow-up rates ranged from 59% to 95% and 5-year follow-up ranged from 48% to 83%. Data completeness rates (ie, the number of cases with available data divided by the expected number of cases) ranged from 66% to 96% for the 1-year follow-up and 60% to 89% for the 5-year follow-up. Patients showed significantly improved postoperative clinical and patient-reported outcomes compared with baseline. The registries serve as a basis for standardised patient monitoring, quality control and answering several clinical questions. With the help of these large databases, clinical practice can be improved for the benefit of our patients.Future plans As the first patients approach the 10-year follow-up landmark, the registry will continue to provide essential data on long-term clinical and patient-reported outcomes, as well as revision rates. In addition to research and quality control, cohort data will be used to enhance real-time clinical decision-making for patients.